0

# How do you solve for x equals y plus 6 and y equals -2-x?

Updated: 12/13/2022

Wiki User

13y ago

4

Buddy Pacocha

Lvl 10
3y ago

Wiki User

13y ago

You have two equations. They are...

x=y+6 Equation (1)

y=-2-x Equation (2)

Since you know what "y" is you can solve by substitution. Substitute the second equation into the first.

x=(-2-x) + 6

x=4-x

2x=4

x=2

Now plug "x" into the second equation to find "y"

y=-2-2

y=-4

Now plug both "x" and "y" into both equations to see if I did them correctly

2=-4+6

2=2 Correct!

-4=-2-2

-4=-4 Correct!

So x=2 and y=-4 are the correct answers.

Earn +20 pts
Q: How do you solve for x equals y plus 6 and y equals -2-x?
Submit
Still have questions?
Related questions

### How do you solve 22 plus 2x equals 37 plus 6 plus x?

22+2x = 37+6+x 2x-x = 37+6-22 x = 21

### Solve 2x plus 8 equals 6?

2x+8 = 6 2x = 6-8 2x = -2 x = -1

### How do you solve 2x-y equals -6 and 2x plus 3y equals 9?

2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9

### How do you solve 2x plus 7 equals 1?

2x + 7 = 1 Therefore, 2x = -6 x = -6/2 x = -3

X=6

### How do you solve 12 equals 2x plus 6?

12 = 2x + 6 subtract 6 from both sides 6 = 2x divide both sides by 2 3 = x

4x=-10 x=-2.5

### Are the graphs of 2x plus 7y equals 6 and 7y equals 2x plus 6 parallel?

Yes, they are. If you solve 2x + 7y = 6 for y, you get y = (-2x + 6) / 7. If you solve 7y + 2x + 6 = 0 for y, you get y = (-2x - 6) / 7. As you can see, both equations have the same slope. Therefore they are parallel. You can punch those equations into a graphing calculator and visually verify that they are indeed parallel.

### What is 2x-6 equals x plus 5?

To solve this equation we have to isolate and solve for x. So: 2x-6= x+5 +6 +6 2x = x+11 -x -x x = 11 So x=11.

### 2x plus 3y equals 6 solve for x?

this can not be solved un less with another equation

### Can You Solve 2x plus 3y equals 18 and 2x-3y equals -6 Using The Elimination Method?

Yes and it works out that x = 3 and y = 4

### Solve-3x-2 equals 2x plus 4 for x?

3x - 2 = 2x + 4 3x - 2x = 4 + 2 x = 6